1991
DOI: 10.1002/1097-4679(199105)47:3<430::aid-jclp2270470317>3.0.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of WISC-R subtest stability in children with learning difficulties

Abstract: The effects of age and IQ level upon the stability of WISC‐R subtests were investigated. The subjects were 130 children with learning difficulties who were referred for a second psychological assessment because of a continuing academic lag. The mean test‐retest interval was 2 years, 8 months. Although the mean change scores for the subtests were relatively small, the standard deviation of the change scores was close to three for most of the subtests. This indicates considerable subtest score fluctuation, with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

1993
1993
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 10 publications
2
8
0
Order By: Relevance
“…Therefore, we used a shortened version of the Wechsler Intelligence Scale for Children, the WISC-R [12]. The WISC-R is suitable for participants of age between 6 years and 16 years 11 months [14] and is agestandardized to compare different age groups with each other [15]. The shortened version of the WISC-R consists of a vocabulary subtest and a block design subtest.…”
Section: Measurementsmentioning
confidence: 99%
“…Therefore, we used a shortened version of the Wechsler Intelligence Scale for Children, the WISC-R [12]. The WISC-R is suitable for participants of age between 6 years and 16 years 11 months [14] and is agestandardized to compare different age groups with each other [15]. The shortened version of the WISC-R consists of a vocabulary subtest and a block design subtest.…”
Section: Measurementsmentioning
confidence: 99%
“…Results of this study indicated that mean VIQ , PIQ and FSIQ scores significantly decreased over administrations by means of3.12, 6.36 and 5.32 points, respectively, over the three-year period. Such results are consistent with previous research investigating the stability of the WISC-R (Bauman , 1991) .…”
Section: Stability Oflo Scores Based On Initial Full Scale Io Scoresupporting
confidence: 93%
“…Based on previous research investigating the stability of scores with the WISC and WISC-R, it was predicted that students receiving an initial FSIQ below 90 would have more stable correlation coefficients than subjects scoring above 109. Results confirmed these previous studies whereby children with initial FSIQ below 90 demonstrated significantly higher test-retest correlation coefficients for VIQ, PIQ and FSIQ scores than children scoring above 109 (Naglieri & pfeiffer, 1983;Bauman, 1991;Klonoff: 1972).…”
Section: Stability Oflo Scores Based On Initial Full Scale Io Scoresupporting
confidence: 87%
See 2 more Smart Citations